Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1120/jacmp.v15i4.4853
|View full text |Cite
|
Sign up to set email alerts
|

The photon dose calculation algorithm used in breast radiotherapy has significant impact on the parameters of radiobiological models

Abstract: The comparison of the pencil beam dose calculation algorithm with modified Batho heterogeneity correction (PBC‐MB) and the analytical anisotropic algorithm (AAA) and the mutual comparison of advanced dose calculation algorithms used in breast radiotherapy have focused on the differences between the physical dose distributions. Studies on the radiobiological impact of the algorithm (both on the tumor control and the moderate breast fibrosis prediction) are lacking. We, therefore, investigated the radiobiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
(83 reference statements)
2
15
0
Order By: Relevance
“…The cohort included patients with both WBO and BSC irradiations, which ensured a representative cross-section of patients from current clinical practice. The results of Paper I predicted increased heterogeneity in the target volume and higher doses to the ipsilateral lung, in agreement with results of other parallel studies comparing the performance of AAA with PBC (Basran et al 2010, Yoo et al 2012, Bufacchi et al 2013, Petillion et al 2014. It is interesting to note that although small, the differences between predictions of the two algorithms were statistically significant in many cases.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The cohort included patients with both WBO and BSC irradiations, which ensured a representative cross-section of patients from current clinical practice. The results of Paper I predicted increased heterogeneity in the target volume and higher doses to the ipsilateral lung, in agreement with results of other parallel studies comparing the performance of AAA with PBC (Basran et al 2010, Yoo et al 2012, Bufacchi et al 2013, Petillion et al 2014. It is interesting to note that although small, the differences between predictions of the two algorithms were statistically significant in many cases.…”
Section: Discussionsupporting
confidence: 79%
“…The range of individual values was rather broad, 4-22% in BSC and 4-44% in WBO. These findings reflect the situation of the normal tissue complication probabilities for the lung where AAA required significantly different model parameters than PBC (Bufacchi et al 2013, Hedin and Back 2013, Petillion et al 2014. Indeed, our findings indicate that the heart could be 13-22% more sensitive that thought based on PBC findings.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Of two other studies related to breast radiotherapy in the first one by Lonski et al 53 the unknown version of the AXB algorithm was shown to be superior in out-of-field dose calculation, when comparing to measurements, the PBC algorithm and the AAA. In the other study by Petillion et al 54 the choice of dose calculation algorithm was shown to have an impact on the parameters of radiobiological models. They suggested that the most accurate solution would be to use the AXB algorithm in Dm,m dose report mode.…”
Section: The Axb Algorithm and Patient Plansmentioning
confidence: 99%